Advokasi Kawasan Tanpa Rokok (KTR) di Kota Banjarbaru: Advocacy for Smoke-Free Areas (SFA) in Banjarbaru City - Khairiyati, Laily; Ali, Indra Haryanto; Khadijah, Siti; Sutaji, Sutaji; Saleha, Anis Kamila (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2026)
One way to protect the public from exposure to cigarette smoke is to implement Smoke-Free Areas (SFAs). This activity was carried out through KTR advocacy in Banjarbaru City for the period May - August 2024. The implementing elements consisted of the Advocacy Team, the Health Office, Regional Work Units (RWUs), educational institutions, religious institutions, and student organizations in Banjarbaru City. The implementation method consisted of Initial Coordination, Audiences and FGD, SFA Task Force Coordination Meetings, Monitoring and Visual Intervention, Educational Socialization in schools, and Institutional Advocacy to RWU. The results of the activity included obtaining permits and directions for SFA activities, gaining support for SFA implementation in 7 settings, strengthening task force coordination, and using cigarette advertising tax data. In addition, it led to the signing of inter-agency commitments, the proposed revisions to the Task Force Decree, and the establishment of an online reporting system. The results of monitoring the implementation of SFA in Public Transportation recorded the highest violation rate at 75%, followed by public places (73.33%) and children's playgrounds (64.29%). Meanwhile, places of worship (40.38%) and workplaces (34.62%) showed moderate levels of violations. The socialization of SFA in schools received a positive response from students and teachers. The advocacy stage of the RWU, through a structural advocacy approach, increased awareness and institutional responsibility for the SFU policy. Strengthening the cross-agency reporting system, providing more extensive educational media in public spaces, and replicating socialization activities across other school levels are needed.